Perencanaan Dan Perancangan Fasilitas Rest Area di Kecamatan Selemadeg Tabanan - I Putu Gede Adi Purusa Maha Wiranata; I Wayan Widanan; I Wayan Runa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
The Denpasar - Gilimanuk highway route crosses the coastal area in the Selemadeg area, Tabanan district. The national road that crosses this coastal area is a road that connects Tabanan Regency & Denpasar City, Bali Province and is an accident-prone route, where there are lack of road facilities such as signs and street lighting at night. The number of bumpy roads accompanied by a forest situation that is often assumed by local people to be a scary situation motivates traffic accidents in this area. When crossing the Denpasar - Gilimanuk highway, there are sporadic locations that provide stopovers or rest areas. Gas stations are also difficult to find along this road. Because of that, Rest & Service Areas (TIP) or generic claims to use a rest area are one of the facilities that must be found on a provincial road. As the name implies, this rest area is used as a resting place for road users. In addition to making human rest, the facilities in the rest area can also be used as a place to rest vehicles. The rest area that you want to build is a type B rest area where the facilities are ATM centers, toilets, stalls or kiosks, minimarkets, prayer rooms, restaurants, green open spaces, & parking lots. This rest area also has natural & culinary tourism, apart from resting, visitors can also enjoy the natural scenery and take selfies in this area.